2009
DOI: 10.1128/jb.00740-09
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Stability of Inducibly ExpressedrpsOmRNA Derivatives inBacillus subtilis

Abstract: The Bacillus subtilis rpsO gene specifies a small (388-nucleotide), monocistronic mRNA that encodes ribosomal protein S15. We showed earlier that rpsO mRNA decay intermediates accumulated to a high level in a strain lacking polynucleotide phosphorylase. Here, we used inducibly expressed derivatives of rpsO, encoding smaller RNAs that had the complex 5 region deleted, to study aspects of mRNA processing in B. subtilis. An IPTG (isopropyl-␤-D-thiogalactopyranoside)-inducible rpsO transcript that contained lac se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Nonetheless, when the initiation codon for translation was mutated in an mRNA with a strong 5= secondary structure, the mRNA half-life was still reduced (49). The latter finding is consistent with the results from studies on the 5=UTR S363 preceding aprE and an artificial stemloop preceding rpsO (82), where the stem-loop and ribosome binding were found to be more important than translation (83).…”
Section: = Untranslated Regions With Other or Unknown Functionssupporting
confidence: 80%
“…Nonetheless, when the initiation codon for translation was mutated in an mRNA with a strong 5= secondary structure, the mRNA half-life was still reduced (49). The latter finding is consistent with the results from studies on the 5=UTR S363 preceding aprE and an artificial stemloop preceding rpsO (82), where the stem-loop and ribosome binding were found to be more important than translation (83).…”
Section: = Untranslated Regions With Other or Unknown Functionssupporting
confidence: 80%
“…However, a model of ribosome-dependent endonucleolytic cleavage by RNase J1 at the upstream boundary of the stalled ribosome is favored by the authors for both ∆ermC and lac-rpsO. 20,22,23 It is not immediately clear to me, however, why these mRNAs would be any different to the cryIIIA and hbs mRNAs. Since the generation of the ribosome-protected species is inhibited by the addition of secondary structures to the 5' end of the ∆ermC and lac-rpsO transcripts, this was interpreted as evidence that the endonucleolytic cleavage by RNase J1 is 5'-end dependent, with the enzyme scanning to the site of ribosome-dependent cutting.…”
Section: Role Of Rnase J1/j2 In the Turnover Of Specific Rnasmentioning
confidence: 90%
“…Two similar examples have been studied by the Bechhofer laboratory: a lac-rpsO fusion in which an inducible lac promoter and a very strong SD (12 nts complementarity to the 3' end of 16S rRNA) was fused to a leaderless rpsO gene 20 and a transcript called ∆ermC, which is stabilized by an erythromycin (Em)-induced stalled ribosome near the 5' end of the transcript. 17 In both cases, a shorter RNA is protected by a ribosome at its 5' end.…”
Section: Role Of Rnase J1/j2 In the Turnover Of Specific Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…More likely, the regulation of mRNA stability by interference with RNase J1 activity occurs at the binding step at the 59 end, upstream of ribosome flow. We have found that, when the same stem-loop structure that is present in the SSL>11 construct was placed at the 59 end of an RNA that has a 59-proximal RNase J1 target site, cleavage by RNase J1 at this site was virtually abolished (Yao and Bechhofer 2009).…”
Section: Discussionmentioning
confidence: 95%